FEATURES OF MEDIA COMPETENCE IN TEACHING BIOLOGY IN CONNECTION WITH PHYSICS (Multidisciplinary Journal of Science and Technology, 2025)
This article provides information on the specific features of media competence in teaching biology and physics, increasing students' interest in education, developing new interactive teaching tools, and using them effectively.